ANALISIS TINGKAT PEMAHAMAN GURU TERHADAP PERENCANAAN PEMBELAJARAN PADA TAMAN KANAK-KANAK DI KOTA PONTIANAK - Utami, Yossy Wirda; Yuniarni, Desni; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractBased on the results of data analysis shows that the level of understanding of teachers in translating the program semester there are 92.7% of respondents who have a moderate understanding. Level of understanding of teachers in interpreting the semester program there are 50% of respondents who have a moderate understanding. Level of understanding of teachers predicted in the semester program there are 50% of respondents who have a moderate understanding. Level of understanding of teachers in translating the RPPM there are 68.75% of respondents who have a moderate understanding. The level of understanding of teachers in interpreting the RPPM there are 53.12% of respondents who have a moderate understanding. The level of understanding of teachers in the forecast in the RPPM there are 69.80% of respondents who have a low understanding. Level of understanding of teachers in translating the RPPH there are 71.8% of respondents who have a moderate understanding. The level of understanding of teachers in interpreting the RPPH there are 55.20% of respondents who have a moderate understanding. The level of understanding of teachers in the forecast in the RPPH there are 57.30% of respondents who have a moderate understanding.Â Keywords: comprehension level, learning planningÂ